2004
DOI: 10.1093/humrep/deh258
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between pregnancy outcome and smooth endoplasmic reticulum clusters in MII human oocytes

Abstract: The presence of sERCs is associated with lower chances of successful pregnancy, even in sERC-negative oocytes from the same cohort that are transferred along with the sERC-positive oocytes. High estradiol levels could be one of the causes of sERC formation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
160
2
5

Year Published

2006
2006
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 171 publications
(181 citation statements)
references
References 33 publications
14
160
2
5
Order By: Relevance
“…1a). The presence of vacuoles or inclusions within the cytoplasm was also considered because the presence of these dysmorphisms is considered an abnormality [42][43][44]49]. Basically, oocytes lacking both vacuoles and inclusions were awarded three points, oocytes with either small amounts of vacuoles or inclusions two points, and oocytes containing both vacuoles and inclusions one point (Fig.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…1a). The presence of vacuoles or inclusions within the cytoplasm was also considered because the presence of these dysmorphisms is considered an abnormality [42][43][44]49]. Basically, oocytes lacking both vacuoles and inclusions were awarded three points, oocytes with either small amounts of vacuoles or inclusions two points, and oocytes containing both vacuoles and inclusions one point (Fig.…”
Section: Methodsmentioning
confidence: 99%
“…Human metaphase II oocytes have distinct morphological characteristics that may be indicative of quality and therefore used to predict implantation potential [21,[36][37][38][39][40][41][42][43]. For example, regular patterns of granularity have been observed in the oocyte cytoplasm and it has been suggested that these patterns correlate with oocyte quality [44,45].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nonetheless, Otsuki et al [26] demonstrated that the presence of SER is associated with lower chances of successful pregnancy and even if normal oocytes from the same IU international units cohort are transferred, pregnancy rates are compromised. Kahraman et al [27] showed that, despite normal pregnancy rates were obtained using oocytes with centrally located granular cytoplasm, more than 50% of pregnancies resulted in abortions and implantation rate was as low as 5%.…”
Section: Discussionmentioning
confidence: 99%
“…Dysmorphic oocytes, i.e., those exhibiting centrally located granular cytoplasm (CLGC) [7], vacuolization [8], or smooth endoplasmic reticulum clusters (sERC) [9,10], are frequently observed [11]. During piezo-ICSI, low-stretching oocytes, which penetrate before piezo pulse application, are also common [12].…”
Section: Introductionmentioning
confidence: 99%